If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 71 = -33 + 8x Reorder the terms: 71 + 4x = -33 + 8x Solving 71 + 4x = -33 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 71 + 4x + -8x = -33 + 8x + -8x Combine like terms: 4x + -8x = -4x 71 + -4x = -33 + 8x + -8x Combine like terms: 8x + -8x = 0 71 + -4x = -33 + 0 71 + -4x = -33 Add '-71' to each side of the equation. 71 + -71 + -4x = -33 + -71 Combine like terms: 71 + -71 = 0 0 + -4x = -33 + -71 -4x = -33 + -71 Combine like terms: -33 + -71 = -104 -4x = -104 Divide each side by '-4'. x = 26 Simplifying x = 26
| 21+3t=9-3t | | 7b+2=13-b | | y(100-y)=2400 | | 5x(5+3x)= | | X*x*x*y=24 | | -10=4+7m | | X+(X+Y)=x | | 7x+8x+1=0 | | 8p-6=12 | | 27x=25 | | K^2+2=3k | | s(t)=-16t^2+144t+180 | | 3(2p+7)+8p(4p-9)= | | x(x+1)(5x+2)=0 | | 6k+10.5k=3K+12 | | K^2+2-3k=0 | | 7+49(2a+15)=-13 | | 2X+2y+z=72 | | 54=3x-30 | | 7+1(11)=P | | 7+1(X)=14 | | -11n-15n=8 | | -9(-5r-6+9m)= | | 7+1(2)=B | | -19=-0.5k | | 12-4x+9=0 | | (55-y)y=684 | | 6g+3g-10+3=47 | | -6x+5(-x+8)=139 | | 15(16)-14=c | | h+13.5=-13.5 | | 15(10)-14=c |